2019
DOI: 10.1055/a-0855-8464
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of pH Sensitive Novel Anticancer Drug Carrier Based on Magnetic Chitosan Quartets

Abstract: Chitosan-coated magnetic nanoparticles are an appropriate drug delivery method which can improve the therapeutic properties of chemotherapy agents and also can be useful as MRI contrast agent for early cancer diagnosis. This research discovers the optimization of the possible therapeutic effects of Chitosan- citric acid- Fe3O4- CUR quartets. Chitosan as a natural polymer can use to encapsulate citric acid modified Fe3O4 nanoparticles. The successful preparation of CUR-loaded nano-carriers was confirmed by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Nanoparticles (NPs), polymer micelles, liposomes, inorganic particles and microemulsion have been used in drug delivery studies. [6][7][8][9][10][11][12][13] Danafar et al- 14,15 prepared anti-tumor nanoparticles using two different pH-responsive materials. They found that the nanoparticles promoted drug release under low pH conditions (pH 5.5), and exhibited an excellent anti-tumor effect on MCF-7 breast cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs), polymer micelles, liposomes, inorganic particles and microemulsion have been used in drug delivery studies. [6][7][8][9][10][11][12][13] Danafar et al- 14,15 prepared anti-tumor nanoparticles using two different pH-responsive materials. They found that the nanoparticles promoted drug release under low pH conditions (pH 5.5), and exhibited an excellent anti-tumor effect on MCF-7 breast cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%